A simple synthetic entryway into new families of NHC–gold-amido complexes and their in vitro antitumor activity. Issue 9 (10th February 2022) - Martynova, Ekaterina A.; Scattolin, Thomas; Cavarzerani, Enrico; Peng, Min; Van Hecke, Kristof; Rizzolio, Flavio; Nolan, Steven P.
Abstract : A simple synthetic pathway to new families of Au–NHC amido complexes under mild reaction conditions is described. Their in vitro anticancer activity was investigated on three human cell lines, showing comparable or even better results than cisplatin. Abstract : A simple synthetic pathway to Au–NHC amido complexes is described. Syntheses and isolation of [Au(NHC)(NR 1 R 2 )] complexes, bearing various NHC ligands and NH-containing heterocycles under mild conditions are reported. The in vitro anticancer activity of these gold-complexes was investigated on three human cancer cell lines. A number of these show comparable or even better antiproliferative activity than cisplatin. Noteworthy is the non-toxicity of most of the complexes on normal cells.